Enhancers of Host Immune Tolerance to Bacterial Infection Discovered Using Linked Computational and Experimental Approaches (Adv. Sci. 26/2022). Issue 26 (15th September 2022) - Sperry, Megan M.; Novak, Richard; Keshari, Vishal; Dinis, Alexandre L. M.; Cartwright, Mark J.; Camacho, Diogo M.; Paré, Jean‐François; Super, Michael; Levin, Michael; Ingber, Donald E.
Abstract : Drug Repurposing Linked computational and experimental approaches identified that Xenopus laevis embryos can naturally tolerate certain bacteria by modulating their metal ion binding and hypoxia gene networks to maintain health despite high pathogen load. In article number 2200222, using natural tolerance mechanisms as inspiration, Megan Sperry, Richard Novak, Donald E. Ingber, and co‐workers induce an artificial tolerant state in susceptible Xenopus using drug repurposing.